The Severity of Acute Kidney and Lung Injuries Induced by Cecal Ligation and Puncture Is Attenuated by Menthol: Role of Proliferating Cell Nuclear Antigen and Apoptotic Markers - Anter, Aliaa; Ahmed, Al-Shaimaa F.; Hammad, Asmaa S. A.; Almalki, Waleed Hassan; Abdel Hafez, Sara Mohamed Naguib; Kasem, AlShaimaa W.; El-Moselhy, Mohamed A.; Alrabia, Mohammad W.; Ibrahim, Ahmed R. N.; El-Daly, Mahmoud (Frontiers in Medicine, 2022)
Objective: Sepsis-induced acute lung injury (ALI) and acute kidney injury (AKI) are major causes of mortality. Menthol is a natural compound that has anti-inflammatory and antioxidative actions. Since exaggerated inflammatory and oxidative stress are characteristics of sepsis, the aim of this study was to evaluate the effect of menthol against sepsis-induced mortality, ALI, and AKI. Methods: The cecal ligation and puncture (CLP) procedure was employed as a model of sepsis. Rats were grouped into sham, sham-Menthol, CLP, and CLP-Menthol (100 mg/kg, p.o). Key findings: A survival study showed that menthol enhanced the survival after sepsis from 0% in septic group to 30%. Septic rats developed histological evidence of ALI and AKI. Menthol markedly suppressed sepsis induced elevation of tissue TNF-a, ameliorated sepsis-induced cleavage of caspase-3 and restored the antiapoptotic marker Bcl2. Significance: We introduced a role of the proliferating cell nuclear antigen (PCNA) in these tissues with a possible link to the damage induced by sepsis. PCNA level was markedly reduced in septic animals and menthol ameliorated this effect. Our data provide novel evidence that menthol protects against organ damage and decreases mortality in experimental sepsis.